The impact of teaching geography according to the Merrill model on the acquisition and retention of concepts among students. Intermediate first grade students (Journal of the College of Basic Education, 2023)
and the lack of knowledge and interest of geography teachers in methods, methods and educational models.modern concepts in the teaching of concepts with their weak knowledge of them, which leads them to interest in the use ofthe usual (traditional) methods, so the following research emphasizes the possibility of teaching onAccording to educational models in acquiring geographic concepts and retaining them among first-grade students.the average, while finding a need to improve these methods and methods used in teaching, and consideringFor the weakness of the effectiveness of teaching (traditional) in the development of students' motivation, the researcher found throughHis work in the field of teaching, his education, and his knowledge of many literatures and previous studies indicate thatStudents tend to memorize automatically and tend to memorize information as an end, with weakness.their participation in the educational process, and through the researcher's observations it was found that the students whoThey learn according to the (traditional) method, they compete to get grades and to gain attentionteachers, and their goal becomes collection only without the help of each other in order to exchangeknowledge, and as a result does not create an atmosphere of scientific competition.